Characterizing Visualization Insights from Quantified-Selfers' Personal Data Presentations - Choe, Eun Kyoung; Lee, Bongshin; schraefel, m.c. (IEEE CG&A Special Issue on Personal Visualization and Visual Analytics, 2015)
Data visualization and analytics research has great potential to empower people to improve their lives. Aiming to design a visualization system to help nonexperts gain and communicate their personal data insights, the authors examined the insights people draw from their personal data and how they communicate them.